2022
DOI: 10.1108/edi-08-2021-0188
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making in the recruitment of women on corporate boards: does gender matter?

Abstract: PurposeThe author provides an insider view of women directors' selections on corporate boards from the empirical setting of India and find if the recruitment practices in this space discriminate against women.Design/methodology/approachThe study collected data from a diverse cohort of 27 directors through semi-structured interviews. The data were analysed by applying an interpretative inductive approach and using the software NVivo's 12-plus version.FindingsThe author’s findings show that board recruiters pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Instead, the analysis indicated that women could dispel gender-based prejudices by altering their behaviours to project male and female traits consistent with the director role. By doing so, the women in this study appear to have deconstructed gendered notions, in line with scholarly arguments of undoing the gender by women managers (Bhardwaj, 2022; Deutch, 2007; Rangwala et al. , 2020).…”
Section: Discussionsupporting
confidence: 67%
“…Instead, the analysis indicated that women could dispel gender-based prejudices by altering their behaviours to project male and female traits consistent with the director role. By doing so, the women in this study appear to have deconstructed gendered notions, in line with scholarly arguments of undoing the gender by women managers (Bhardwaj, 2022; Deutch, 2007; Rangwala et al. , 2020).…”
Section: Discussionsupporting
confidence: 67%
“…As the requirements are listed, male candidates may find more advantages in certain qualifications. Aspects unrelated to performance, such as high emphasis on leadership style, previous job title, or years of experience, benefit male applicants more [3]. The job title may include words like "Director," "Vice President," "Manager," or "Executive," depending on the level of the position.…”
Section: Introductionmentioning
confidence: 99%
“…Sraieb and Akin (2021) find evidence linking female directors to positive correlations with corporate environmental performance. The board of directors serves as an internal oversight mechanism for corporate governance, acting as a source of sustainable competitive advantage, particularly in monitoring financial policy reporting (Bhardwaj, 2022). Women on the board positively impact sustainable company performance (Guizani and Abdalkrim, 2022).…”
Section: Introductionmentioning
confidence: 99%